2019
DOI: 10.1108/lodj-11-2018-0417
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of ethical leadership: the theory of planned behavior

Abstract: Purpose The purpose of this paper is to examine the antecedents of ethical leadership by drawing on the theory of planned behavior (TPB). The authors hypothesized that a leader’s attitude toward ethical behavior, subjective norm about ethical behavior and perceived behavioral control relate to his/her ethical intention and subsequently to the follower’s perceptions of ethical leadership. Design/methodology/approach The authors found general support for the model using data collected from a two-wave and two-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Results showed that ethical leadership had the strongest positive correlation with subjective norms, as informal pressure from supervisors was usually a positive force, especially during change management. The positive correlation of ethical leadership with attitude, subjective norms, and perceived behavioral control was evidenced, similar to existing literature [72][73][74]. Qin et al [72] surveyed workers from hotels and golf clubs in China and observed that ethical leadership improved workers' customer-oriented behavior through their individual work attitudes.…”
Section: Statistical Fitnesssupporting
confidence: 82%
See 1 more Smart Citation
“…Results showed that ethical leadership had the strongest positive correlation with subjective norms, as informal pressure from supervisors was usually a positive force, especially during change management. The positive correlation of ethical leadership with attitude, subjective norms, and perceived behavioral control was evidenced, similar to existing literature [72][73][74]. Qin et al [72] surveyed workers from hotels and golf clubs in China and observed that ethical leadership improved workers' customer-oriented behavior through their individual work attitudes.…”
Section: Statistical Fitnesssupporting
confidence: 82%
“…At the same time, the field of ethical leadership was broad and developing. Although uncommon, attempts were made to bridge ethical leadership and the theory of planned behavior [72][73][74]. The focus of this research aimed to apply the theory of planned behavior and ethical leadership to determine the factors influencing the adoption of environmental protection behaviors in a hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Harnessing the benefits of creative deviance and avoiding its damages are thus a big challenge for the leaders and the integrity of leaders is essential in this context. Previous research has acknowledged that leadership plays a crucial role in nurturing positive employee behavior including creativity (Afsar and Shahjehan, 2018;Amundsen and Martinsen, 2015;Gong et al, 2009;Rahaman et al, 2019;Shafique et al, 2019), however, limited attention from researchers has been paid to examining the relationship between ethical leadership and creative deviance.…”
Section: Introductionmentioning
confidence: 99%
“…Ajzen's theory has been repeatedly verified, a meta-analysis carried out by Armitage showed the high effectiveness of the model in predicting behaviour and intentions (Armitage & Conner, 2001). The model was previously used for the research of unethical activities related to corruption (Rabl & K€ uhlmann, 2009) and tax compliance intentions (Benk et al, 2011), mostly because it provides an appropriate fit for modelling individual ethical reasoning (Fleischman & Valentine, 2019;Rahaman et al, 2019).…”
Section: Methodsmentioning
confidence: 94%